SHIFT IN FAMILY VALUES: CHALLENGES AND ADAPTATIONS IN THE MODERN ERA - Desi Ayu Fitria Salim; Novia Ardana; Silvani Tiara Afrianda (OPINI: Journal of Communication and Social Science, 2024)
The shift in family values has become an important phenomenon in the social context of the modern era. This study examines the changes in values that occur within families, the challenges they face, and the adaptation strategies employed by families to remain harmonious and functional. In the context of modernization, globalization, and technological advancement, traditional values such as family unity, respect for parents, and clear gender roles are undergoing significant transformations. This research uses a qualitative method with a case study approach on several families in Indonesia. Data were collected through in-depth interviews and participatory observation to gain a comprehensive understanding of the current dynamics of family values. The results of the study show that although many families experience dilemmas in maintaining traditional values, they also demonstrate a high capacity for adaptation by integrating new values relevant to the modern context